The Role of Probiotics as Adjuvant Therapy for Irritable Bowel Syndrome in Children - Ananda Rizky (Journal of World Science, 2025)
Irritable Bowel Syndrome (IBS) is a functional gastrointestinal disorder (GGIF) that is not caused by disease or organ damage. The exact pathophysiological mechanisms underlying IBS are still unknown. The pathogenesis of IBS involves alterations of gastrointestinal motility, post-infection reactivity, visceral hypersensitivity, gut-brain interactions, microbiota dysbiosis, bacterial overgrowth in the small intestine, sensitivity to food, carbohydrate malabsorption, and intestinal inflammation. Evidence of the efficacy of most pharmacological treatments for IBS is still weak, leading to unsatisfactory symptom control or the possibility of adverse reactions in many patients. The method of writing this article is in the form of a narrative review from various sources including google scholar, PubMed, and science direct with the keywords "irritable bowel syndrome" and "child" to summarize the role of probiotics as adjuvant therapy in the management of IBS in children. Probiotics are emerging as a new therapeutic option in gastrointestinal functional disorders (GGIF), along with the recognition of the importance of the gut microbiota in influencing brain-gut interactions, as well as the role of intestinal infections in the genetics of post-infectious gastrointestinal functional disorder (GGIF-PI). Therefore, probiotics have the potential to play a relevant role in the management of GGIF, both through their effects on the gut microbiota and through alterations of brain function and pain perception centrally.